INADMISSIBLE MEMORY “OPERATIONS”: REPRESSIONS AGAINST THE GREEKS IN UKRAINET - Anna Hedo; Iryna Gridina (Київські історичні студії, 2019)
The study illustrates the preparation and conduct of «national operations» during the «Great Terror» of 1937–1938 and shows the course and causes of the so-called «Greek Operation». The motives that guided the Stalinist leadership, repressing the Greek population of Ukraine, in particular, Stalin’s desire to retaliate against the Soviet Greeks for the failure of the special operation in Greece, were noted (in 1935 a monarchy was restored in Greece, which led to the prohibition and deepening of the Communist Party of Greece into the underground, from which it had some plans to spread influence over the Southeast and South America). Inventing a variety of factors and reasons to eliminate economically sound and culturally organized national minority, and therefore «dangerous» and unacceptable for building a homogeneously unified Soviet society in the face of fear for the most part mythical enemy, translating all miscalculations into «fifth column», led to unjustified accusations, mass arrests, terrible sentences to the Greek population of Ukraine.The appeal to the history of Stalin’s repression against the backdrop of Russia’s hybrid war against Ukraine is urgent. The «Renaissance of Stalinism» in Russia, even with its imaginative symbolism, which rehabilitates Stalin’s role in political repression, embodies Stalinist themes in the form of visual propaganda, is a component of Russian-Ukrainian memory wars. The manipulation of historical memory, the attempt to interpret contemporary events and processes in the light of ideas inherited from the USSR are part of a strategy to restore Russia’s status as a world leader, where the figure of Stalin and the rehabilitation of Stalinist politics play a lasting role. It should be clearly understood that manipulating commemorative practices in times of war is nothing more than military «operations.» In the case of Stalinist repression, in particular against national minorities, it is not simply an effort to justify them in the past, but a preparation for resolution in the future. The memory of the Great Terror at the center of which is the population of Ukraine is the most important component of our country’s humanitarian security and historical policy.